Pelatihan Pembuatan Blog Pembelajaran Guru MGMP PKn SMA/SMK/MA Se-Kabupaten Ogan Ilir - Hardini Novianty; Pacu Putra; Dinna Yunika; Allsela Meiriza; Rahmat Izwan Heroza; Ari Wedhasmara; M. Ihsan Jambak (Annual Research Seminar (ARS), 2015)
Nowadays, there are some changeness in paradigm of educational area, where peoples are involved in educational area should give pressure of student’s cognitive and affectives, especially how affect student’s thinking and studying method that can increase their analitic skill, critic skill, problem solving, and communication for reaching out their thinking behaviourTeacher as a mediator in delivering teaching material should be able deliver and present that teaching material that can motivate student in teaching process. In this case, teacher should be able to use information technology in delivering and presenting teaching material, so teaching material will be easy to be understood by studentIn this dedication for society activity was held for helping teachers in Kabupaten Ogan Ilir in delivering teaching material by using blogAs a result, Teacher increase their skill in making teaching blog. It shows that respond from teachers that follow this activity are very pleasure. As a feedback from teachers of this activity feel their teaching skill quality was increased by follow this activity